Estimates of bending moments and pressures due to slamming - Glover, Robert E. (Robert Ellsworth), 1896-1984, author; Colorado State University, Department of Civil Engineering, publisher (Colorado State University. Libraries, 1958)
The bending moments which can be applied to the ship's structure and the pressures which can be applied to the ship's plates as a result of slamming are estimated from hydrodynamical considerations.
CER58REG24 annotated with (a).
Technical Note.
Prepared for David Taylor Model Basin.
Keywords: Bending moment; Ships -- Hydrodynamic impact; Naval architecture -- Research